2023
DOI: 10.1111/joim.13629
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis: Epidemiology and clinical insights

Abstract: Sarcoidosis is characterized by noncaseating granulomas which form in almost any part of the body, primarily in the lungs and/or thoracic lymph nodes. Environmental exposures in genetically susceptible individuals are believed to cause sarcoidosis. There is variation in incidence and prevalence by region and race. Males and females are almost equally affected, although disease peaks at a later age in females than in males. The heterogeneity of presentation and disease course can make diagnosis and treatment ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 131 publications
(185 reference statements)
0
23
0
2
Order By: Relevance
“…In comparison with prevalence studies, a lower proportion is expected due to a better prognosis of sarcoidosis. 35 Moreover, the incidence and prevalence of sarcoidosis vary across regions and even within countries. 35 In Brazil, the epidemiology of sarcoidosis is largely unknown.…”
Section: Discussionmentioning
confidence: 99%

Relative incidence of interstitial lung diseases in Brazil

Lobo Krupok Matias1,
Alberto de Castro Pereira1,
Raquel Soares1
et al. 2024
J Bras Pneumol.
“…In comparison with prevalence studies, a lower proportion is expected due to a better prognosis of sarcoidosis. 35 Moreover, the incidence and prevalence of sarcoidosis vary across regions and even within countries. 35 In Brazil, the epidemiology of sarcoidosis is largely unknown.…”
Section: Discussionmentioning
confidence: 99%

Relative incidence of interstitial lung diseases in Brazil

Lobo Krupok Matias1,
Alberto de Castro Pereira1,
Raquel Soares1
et al. 2024
J Bras Pneumol.
“…These activated cells discharge various mediators, including cytokines, chemokines, and reactive oxygen species that may be involved in the progression of disease . Many studies hypothesized that genetic susceptibility, environmental factors, putative antigens and autoimmunity in the development of this diseases [19].Infectious agents,Noninfectious agents,Immune-related diseases and Cancer were mentioned for differential diagnosis of sarcoidosis [20].Neurological involvement in sarcoidosis is relatively uncommon, with a reported prevalence of 3 to 10% [21].Neurological manifestations are rarely the first or only symptom of sarcoidosis,with 84 to 94 percent of cases experiencing coexisting systemic manifestations, especially in the lungs and intrathoracic lymph nodes [22]. The patient in this case recovered well,After a period of treatment,her daily life significantly unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence regarding the link between physical activity, obesity and sarcoidosis is limited and inconclusive. [68][69][70][71] While two cohort studies involving a large number of women identified a positive relationship between weight gain and adult obesity with heightened sarcoidosis incidence, 68,69 a nested case-control study observed a positive association for obesity but not for overweight 72 and a retrospective case-control study observed no significant association between elevated BMI and sarcoidosis risk 70 . Such discrepancies might stem from the imprecision of BMI as a measure of obesity or variations in study populations.…”
Section: Physical Activity Obesity and Sarcoidosismentioning
confidence: 99%